Analisis komoditas unggulan agribisnis dan pengembangannya pada sentra produksi Kota Sungai Penuh - Yuvanda, Sesraria (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to determine the selected agribusiness commodities to be developed and analyze the production and marketing for current and future conditions. The Simple Additive Weighting (SAW) model is used to determine the only things of agribusiness, while the analysis of production and marketing development uses a qualitative descriptive analysis model. The results showed that the selected superior commodities were Chili with the first rank, Coffee in the second rank, Cinnamon in the third rank, and Potato in the fourth rank. Production and marketing conditions now show no increase in added value and the role of cooperatives. Production and marketing in the future that is desired must increase added value and market control through cooperatives. Â